ANALISIS PENGARUH SIKAP GENERASI MILENIAL TERHADAP MINAT MELAKUKAN USAHA TANI DI DESA LAPODI KECAMATAN PASAR WAJO KABUPATEN BUTON - Suriadi Suriadi; Rabiyatul Jasiyah (Media Agribisnis, 2020)
This study aims to determine the effect of the attitude of the millennial generation on the interest in farming in Lapodi village. This research was conducted in Lapodi village, Pasarwajo sub-district, Buton regency from February to March 2020. The sample of this research is all millennial farmers in Lapodi village with a total of 44 people. The technique of collecting data is using a questionnaire. The data analysis technique uses multiple linear regression analysis, with the help of the SPSS 16.0 application. In the SPSS application, the analysis used is the validity test, reliability test, normality test, t-sample test, ANOVA, coefficients, and r-square test. The results showed that the attitude of the millennial generation had a significant effect on the interest in doing agricultural business, this can be seen from the results of the SPSS printout where T count = 2,850 > T table (0,05) = 2,000. Thus H0 is rejected and H1 is accepted, which states that the higher the attitude of the millennial generation to do agricultural business. The influence of the attitude of the millennial generation on the interest of agricultural enterprises of 40.3% while 59.7% is influenced by other factors that are not included in this research model. Keywords: Millennial generation, attitudes, interests farming